Unlocking the role of lactate: metabolic pathways, signaling, and gene regulation in postmitotic retinal cells - Rajala, Raju V. S.; Rajala, Ammaji (Frontiers in Ophthalmology, 2023)
The Warburg effect, which was first described a century ago, asserts that mitotic tumor cells generate higher quantities of lactate. Intriguingly, even in typical physiological circumstances, postmitotic retinal photoreceptor cells also produce elevated levels of lactate. Initially classified as metabolic waste, lactate has since gained recognition as a significant intracellular signaling mediator and extracellular ligand. This current review endeavors to provide a concise overview and discourse on the following topics: the localization of lactate-producing enzymes, the 2 functional significance of these enzymes, the signaling functions of lactate, and its impact on the gene expression of photoreceptors in retinal cells.